Method for preparing diamond coating through laser cladding

By preparing a gradient transition layer on the surface of cemented carbide and combining laser cladding technology with rare earth oxides, diamond coating with excellent mechanical properties and high binding strength was prepared, which solved the problem of insufficient binding force between diamond coating and cemented carbide, extended service life and improved processing quality.

CN119843275AActive Publication Date: 2025-04-18HUNAN LIANGCHENG NEW MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510315121.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The insufficient bonding force between diamond coating and cemented carbide limits its expansion in the field of processing. How to improve the mechanical properties and bonding strength of diamond coating has become the focus of research.

Method used

The diamond coating is prepared by laser cladding technology, and a gradient transition layer is prepared on the surface of the substrate, and the pre-coated diamond, alloy powder and rare earth oxide are mixed into laser cladding powder, cladding is carried out under the protection of inert gas, and then annealing is carried out to improve the bonding strength.

Benefits of technology

It significantly improves the mechanical properties and bonding strength of the diamond coating, extends the service life of the cemented carbide matrix, avoids the peeling of the diamond coating, and improves the processing quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a method for preparing a diamond coating through laser cladding, which comprises the following steps: polishing and cleaning the surface of a base material, preparing a gradient transition layer on the surface of the base material, mixing pre-coated diamond, alloy powder and rare earth oxide to obtain laser cladding powder, and carrying out laser cladding on the laser cladding powder to obtain the diamond coating. Laser cladding powder is cladded on the gradient transition layer under the protection of inert gas to form the diamond coating, then the diamond coating is subjected to annealing treatment, and the prepared diamond coating has excellent mechanical property and bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a method for preparing a diamond coating by laser cladding. Background Art

[0002] Diamond coating on the surface of cemented carbide can significantly increase the service life of tools and machine tool parts, improve the surface roughness and improve the processing quality. However, due to the insufficient bonding force between diamond coating and cemented carbide, its further expansion in the processing field is limited. How to improve the mechanical properties of diamond coating and improve the bonding strength between it and cemented carbide and extend its service life has become the current research focus. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing diamond coating by laser cladding.

[0004] The technical solutions adopted are as follows: A method for preparing a diamond coating by laser cladding comprises the following steps: S1: polishing and cleaning the surface of the substrate; S2: preparing a gradient transition layer on the surface of the substrate, wherein the gradient transition layer sequentially comprises a first transition layer containing metal carbides and a second transition layer containing metal carbides and metal nitrides; S3: dispersing diamond nanopowder in a solvent, adding 1-butyl-3-vinylimidazole tetrafluoroborate, divinylbenzene and a free radical initiator, heating the reaction, returning to room temperature, collecting the precipitate and vacuum drying to obtain a pre-coated diamond; S4: mixing the pre-coated diamond, alloy powder and rare earth oxide to obtain laser cladding powder; S5: using a coaxial powder feeding laser cladding device to clad the laser cladding powder on the gradient transition layer under the protection of an inert gas to form a diamond coating; S6: The diamond coating is then annealed at a temperature of 600-900° C. for a time of 60-180 min.

[0005] Furthermore, the substrate is YG8 cemented carbide.

[0006] Furthermore, the first transition layer is composed of titanium carbide, tungsten carbide and metallic titanium in a mass ratio of 1-5:1-5:1-5.

[0007] Furthermore, the second transition layer is composed of titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metallic titanium in a mass ratio of 1-5:1-5:1-5:1-5:1-5.

[0008] Furthermore, the molar ratio of 1-butyl-3-vinylimidazole tetrafluoroborate to divinylbenzene is 1-10:1.

[0009] Furthermore, in S3, the solvent consists of anhydrous ethanol, deionized water and acetonitrile; and the temperature-raising reaction is carried out by heating the temperature to 70-75° C. for 12-48 hours.

[0010] Furthermore, the mass ratio of the pre-coated diamond, alloy powder and rare earth oxide is 1-4:5-10:0.1-0.3.

[0011] Furthermore, the alloy powder is 718 nickel alloy powder.

[0012] Furthermore, the rare earth oxide is lanthanum oxide and / or cerium oxide.

[0013] Furthermore, in S5, the laser power is 1000-3000W, the spot diameter is 5-10mm, the powder feeding rate is 10-50g / min, and the scanning speed is 180-300mm / min.

[0014] Beneficial effects of the present invention: The present invention provides a method for preparing a diamond coating by laser cladding. The prepared diamond coating has excellent mechanical properties and bonding strength, and can effectively extend the service life of a cemented carbide substrate. Polishing and cleaning the substrate together can form micron-level roughness on the substrate surface, increase the mechanical bite area of ​​the gradient transition layer, and improve the bite strength. The gradient transition layer can achieve a gradual match between the thermal expansion coefficient and chemical compatibility of the substrate and the diamond coating, reduce interface stress, avoid diamond coating peeling, and extend service life; By coating diamond nanopowder with polyionic liquid, on the one hand, the burning of diamond during the cladding process is reduced and the graphitization of diamond is inhibited. On the other hand, the active boron atoms and carbon atoms produced by the decomposition of polyionic liquid during laser cladding can react with alloy powder to generate corresponding borides and carbides, improve the wettability of diamond and metal melt, fill the interface gap, and enhance the bonding strength. By adding rare earth oxides, the distribution of diamond in the molten pool can be significantly improved, avoiding segregation due to density differences. At the same time, rare earth elements can promote interface reactions and enhance the bonding strength of diamond coatings. Annealing can eliminate residual stress, significantly change the microstructure of diamond coatings, stabilize the size, reduce deformation and crack tendency, and eliminate tissue defects, which plays a positive role in improving the mechanical properties and bonding strength of diamond coatings. DETAILED DESCRIPTION

[0015] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0016] Embodiment 1: A method for preparing a diamond coating by laser cladding comprises the following steps: S1: Using YG8 cemented carbide as the substrate, the substrate was polished to a surface roughness of 4.5 μm, then ultrasonically cleaned with acetone and anhydrous ethanol in turn, and then the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and then dried in a vacuum to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide with a mass ratio of 3:7:0.2 were fully ball-milled to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. min, and then the diamond coating was annealed at a temperature of 800°C for 80 min.

[0017] Embodiment 2: The method is substantially the same as Example 1, except that cerium oxide is used instead of lanthanum oxide; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: YG8 cemented carbide was used as the substrate, and the substrate was polished to a surface roughness of 4.5 μm. Then, it was ultrasonically cleaned with acetone and anhydrous ethanol in sequence, and the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and then dried in a vacuum to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and cerium oxide with a mass ratio of 3:7:0.2 were fully ball-milled and mixed to obtain laser cladding powder. The laser cladding powder was clad on the second transition layer under argon protection using a coaxial powder feeding laser cladding equipment to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. min, and then the diamond coating was annealed at a temperature of 800°C for 80 min.

[0018] Embodiment 3: The method is basically the same as Example 1, except that the mass ratio of the pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide is adjusted to 3:7:0.1; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: Using YG8 cemented carbide as the substrate, the substrate was polished to a surface roughness of 4.5 μm, then ultrasonically cleaned with acetone and anhydrous ethanol in turn, and then the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and vacuum dried to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide with a mass ratio of 3:7:0.1 were fully ball-milled and mixed to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. min, and then the diamond coating was annealed at a temperature of 800°C for 80 min.

[0019] Embodiment 4: The method is basically the same as Example 1, except that the mass ratio of the pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide is adjusted to 3:7:0.3; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: Using YG8 cemented carbide as the substrate, the substrate was polished to a surface roughness of 4.5 μm, then ultrasonically cleaned with acetone and anhydrous ethanol in turn, and then the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and vacuum dried to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide with a mass ratio of 3:7:0.3 were fully ball-milled and mixed to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. min, and then the diamond coating was annealed at a temperature of 800°C for 80 min.

[0020] Comparative Example 1: It is basically the same as Example 1, except that it does not contain a gradient transition layer; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: YG8 cemented carbide was used as the substrate, and the substrate was polished to a surface roughness of 4.5 μm. Then, it was ultrasonically cleaned with acetone and anhydrous ethanol in sequence, and the surface was dried with a hot air blower; S2: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and vacuum dried to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide with a mass ratio of 3:7:0.2 were mixed by ball milling to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. min, and then the diamond coating was annealed at a temperature of 800°C for 80 min.

[0021] Comparative Example 2: The method is basically the same as Example 1, except that the diamond nanopowder is not pre-coated; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: YG8 cemented carbide was used as the substrate, and the substrate was polished to a surface roughness of 4.5 μm. Then, it was ultrasonically cleaned with acetone and anhydrous ethanol in sequence, and the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, the gradient transition layer sequentially comprising a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, a coaxial powder feeding laser cladding device is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, a coaxial powder feeding laser cladding device is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. S3: Diamond nano-powder, inconel 718 nickel alloy powder and lanthanum oxide in a mass ratio of 3:7:0.2 were fully ball-milled and mixed to obtain laser cladding powder. Coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120 μm. The laser power was 3000 W, the spot diameter was 5 mm, the powder feeding rate was 10 g / min, the scanning speed was 200 mm / min, and then the diamond coating was annealed at a temperature of 800 °C and an annealing time of 80 min.

[0022] Comparative Example 3: The method is substantially the same as Example 1, except that lanthanum oxide is not contained; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: YG8 cemented carbide was used as the substrate, and the substrate was polished to a surface roughness of 4.5 μm. Then, it was ultrasonically cleaned with acetone and anhydrous ethanol in sequence, and the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and then dried in a vacuum to obtain pre-coated diamond. The pre-coated diamond and inconel 718 nickel alloy powder with a mass ratio of 3:7 were fully ball-milled and mixed to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min. The diamond coating was then annealed at a temperature of 800℃ and an annealing time of 80min.

[0023] Comparative Example 4: The method is basically the same as Example 1, except that no annealing treatment is performed; A method for preparing a diamond coating by laser cladding comprises the following steps: S1: Using YG8 cemented carbide as the substrate, the substrate was polished to a surface roughness of 4.5 μm, then ultrasonically cleaned with acetone and anhydrous ethanol in turn, and then the surface was dried with a hot air blower; S2: A gradient transition layer is prepared on the surface of the substrate, and the gradient transition layer includes a first transition layer with a thickness of 250 μm and a second transition layer with a thickness of 100 μm. When preparing the first transition layer, titanium carbide, tungsten carbide and metal titanium powder with a mass ratio of 1:1:2 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the substrate under the protection of argon gas to form the first transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min. When preparing the second transition layer, titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metal titanium powder with a mass ratio of 1:1:1:1:4 are used as raw materials. After being fully ball-milled, coaxial powder feeding laser cladding equipment is used to laser-clad the raw materials on the surface of the first transition layer under the protection of argon gas to form the second transition layer. The laser power is 2000 W, the spot diameter is 5 mm, the powder feeding rate is 20 g / min, and the scanning speed is 200 mm / min; S3: 1g of diamond nanopowder was dispersed in a mixed solvent consisting of 10ml of anhydrous ethanol, 10ml of deionized water and 20ml of acetonitrile, and then 10mmol of 1-butyl-3-vinyl imidazole tetrafluoroborate, 5mmol of divinylbenzene and 5mmol of azobisisobutyronitrile were added. The temperature was raised to 75℃ for reaction for 24h and then returned to room temperature. The precipitate was collected, washed with anhydrous ethanol and then dried in a vacuum to obtain pre-coated diamond. The pre-coated diamond, inconel 718 nickel alloy powder and lanthanum oxide with a mass ratio of 3:7:0.2 were fully ball-milled and mixed to obtain laser cladding powder. The coaxial powder feeding laser cladding equipment was used to clad the laser cladding powder on the second transition layer under argon protection to form a diamond coating with a thickness of 120μm. The laser power was 3000W, the spot diameter was 5mm, the powder feeding rate was 10g / min, and the scanning speed was 200mm / min.

[0024] Performance Testing: The samples prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to relevant performance tests; The microhardness of the diamond coating on the sample surface was measured using a 600MRD-S Rockwell hardness tester. The diamond coating was subjected to a friction test using a UMT friction and wear tester from the German company BRUKER (reciprocating friction and wear, plane contact, a Φ 7.938 mm silicon nitride ball, a load of 120 N, a time of 30 min, and a steel ball reciprocating speed of 10 mm / s).

[0025] The Rockwell indentation method was used to evaluate the combined performance. The Rockwell indentation was made on the diamond coating using a 671 HRS-150 digital Rockwell hardness tester produced by Laizhou Huayin Testing Instrument Co., Ltd., and the indentation was observed under a microscope. The top angle of the diamond indenter used was 120°±20′, the applied load was 1470 N, and the loading time was 10 s.

[0026] The results of the above tests are shown in Table 1 below: Table 1:

[0027] Note: VDI 3198-1992 standard divides coating adhesion into four levels: HF1, HF2, HF3 and HF4, among which HF1 has the strongest adhesion and HF4 has the weakest adhesion; From the comparison of Examples 1, 3-4 in Table 1 above, it can be seen that different amounts of lanthanum oxide added will affect the mechanical properties of the diamond coating; From the comparison between Examples 1 and 2 in Table 1 above, it can be seen that adding cerium oxide instead of lanthanum oxide will deteriorate the mechanical properties of the diamond coating; From the comparison between Example 1 and Comparative Example 1 in Table 1 above, it can be seen that the setting of the gradient transition layer can greatly improve the bonding strength of the diamond coating; From the comparison between Example 1 and Comparative Example 2 in Table 1 above, it can be seen that the pre-coating treatment of diamond nanopowder plays a positive role in improving the mechanical properties of the diamond coating; From the comparison between Example 1 and Comparative Example 3 in Table 1 above, it can be seen that the addition of lanthanum oxide plays a positive role in improving the mechanical properties of the diamond coating; From the comparison between Example 1 and Comparative Example 4 in Table 1 above, it can be seen that annealing treatment plays a positive role in improving the mechanical properties of the diamond coating.

[0028] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a diamond coating by laser cladding, characterized in that: The following steps are involved: S1: polishing and cleaning the surface of the substrate; S2: preparing a gradient transition layer on the surface of the substrate, wherein the gradient transition layer sequentially comprises a first transition layer containing metal carbides and a second transition layer containing metal carbides and metal nitrides; S3: dispersing diamond nanopowder in a solvent, adding 1-butyl-3-vinylimidazole tetrafluoroborate, divinylbenzene and a free radical initiator, heating the reaction, returning to room temperature, collecting the precipitate and vacuum drying to obtain a pre-coated diamond; S4: mixing the pre-coated diamond, alloy powder and rare earth oxide to obtain laser cladding powder; S5: using a coaxial powder feeding laser cladding device to clad the laser cladding powder on the gradient transition layer under the protection of an inert gas to form a diamond coating; S6: The diamond coating is then annealed at a temperature of 600-900° C. for a time of 60-180 min.

2. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: The substrate is YG8 cemented carbide.

3. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: The first transition layer is composed of titanium carbide, tungsten carbide and metallic titanium in a mass ratio of 1-5:1-5:1-5.

4. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: The second transition layer is composed of titanium carbide, tungsten carbide, titanium nitride, chromium nitride and metallic titanium in a mass ratio of 1-5:1-5:1-5:1-5:1-5.

5. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: The molar ratio of 1-butyl-3-vinylimidazole tetrafluoroborate to divinylbenzene is 1-10:

1.

6. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: In S3, the solvent consists of anhydrous ethanol, deionized water and acetonitrile; the temperature-raising reaction is to raise the temperature to 70-75° C. and react for 12-48 hours.

7. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: The mass ratio of the pre-coated diamond, alloy powder and rare earth oxide is 1-4:5-10:0.1-0.

3.

8. The method for preparing a diamond coating by laser cladding according to claim 7, characterized in that: The alloy powder is 718 nickel alloy powder.

9. The method for preparing a diamond coating by laser cladding according to claim 7, characterized in that: The rare earth oxide is lanthanum oxide and / or cerium oxide.

10. The method for preparing a diamond coating by laser cladding according to claim 1, characterized in that: In S5, the laser power is 1000-3000W, the spot diameter is 5-10mm, the powder feeding rate is 10-50g / min, and the scanning speed is 180-300mm / min.

Citation Information

Patent Citations

  • Micro / nano textured diamond-like-ionic liquid composite film and preparation method thereof

    CN103192561A

  • Production method of diamond-like carbon film

    CN105887051A

  • High-strength wear-resistant closed steel frame and machining process thereof

    CN113215566A

  • Super wear-resistant composite coating and coating process

    CN114959700A

  • Preparation method of high-wear-resistance thermal spraying powder

    CN115255355A